Pengaruh Content Marketing dan Online Customer Review Terhadap Minat Beli Konsumen Pada Produk Indomilk Durian Musang King di TikTok Shop (Studi Pada Konsumen Kecamatan Babelan) - Ahmed Ferdi Firdaus; Sukirno (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.Online shopping platforms have reshaped consumer behavior, prompting companies to adopt interactiveand experience-based promotional strategies. This study aimed to analyze the influence of contentmarketing and online customer reviews on consumer purchase intentions for Indomilk Durian Musang Kingproducts on TikTok Shop, focusing on consumers in Babelan District. Using a quantitative survey method,data were collected from 110 respondents who had purchased Indomilk and seen advertisements for theDurian Musang King variant. Multiple linear regression was used for data analysis. The findings revealed thatcontent marketing (X1) had a positive and significant partial effect on purchase intention by 50.3%, whileonline customer reviews (X2) had a stronger positive effect of 66.8%. Simultaneously, both variables influenced purchase intention (Y) by 67.8%, with the remaining 32.2% attributed to other factors not studied, such as price, product quality, and brand image. These results highlight the strong role of digitalengagement in driving consumer decisions. Keywords: Content Marketing, Online Customer Reviews, Purchase Intention